Along the fringes of Agency: neurodevelopmental account of the obsessive mind. (24th October 2022) - Poletti, Michele; Gebhardt, Eva; Raballo, Andrea
Abstract: The experiential core of the obsessive mind rests on subtle, primary mental phenomena (such as obsessions and so called "sensory phenomena") which precede and trigger behavioral compulsions. Converging evidence supports a possible pathophysiological role for altered corollary discharge (phenotypically expressed in sensorimotor symptoms and contributing to a reduced Sense of Agency [SoA]), in the neurodevelopment of obsessions and "sensory phenomena." In phenomenological terms, "sensory phenomena" may represent the subjective experiential resonance of an individual history of persistent inaccurate sensory predictions, whereas accompanying manifestations, such as the obsessive need for order and symmetry, may represent a compensatory attempt to mitigate "sensory phenomena" (eg, by increasing the sensory predictability of the surrounding world). Since disturbances of both SoA and Sense of Ownership have been thematized as potential pathogenetic factors in the neurodevelopment of the psychotic mind, a dimensional account of altered sensorimotor prediction may partly explain the affinities (and high comorbidity) between obsessive–compulsive disorder and schizophrenia spectrum disorders.